Long-term evolution of the subsidiary's role: A qualitative perspective on a subsidiary located in Poland - Marlena Dzikowska; Marian Gorynia (International Journal of Management and Economics, 2020)
So far, very little attention has been paid to the roles of foreign subsidiaries located in Poland and if or how these roles have evolved. Simultaneously, there exists strong empirical justification for assuming these roles have been evolving over the years. Through a literature review and empirical case study of a foreign subsidiary located in Poland, this study analyzes the evolution of the subsidiary role and indicates its relations with groups of external and internal determinants. The case study examines a 10-year period of operations of a foreign subsidiary active in the automotive industry. The results indicate that the evolution of the subsidiary role encompasses factors such as markets served, functional areas of operations, and complexity of operations. The presented case study describes the complex relations among factors related to the subsidiary, HQ, and environment concerning the evolution of the subsidiary role.
Keywords: F23; F61; 650; foreign subsidiary; Poland; multinational enterprise; MNE; evolution of a subsidiary; subsidiary role; value chain